Color Code with a Logical Control- S Gate Using Transversal T Rotations - Brown, Benjamin J. (Physical review letters, 2025)
The color code has been invaluable for the development of the theory of fault-tolerant logic gates using transversal rotations. Three-dimensional examples of the color code have shown us how its structure, specifically the intersection of the supports of logical operators, can give rise to non-Clifford T and CCZ gates. Here we present a color code with a logical control-S gate that is accomplished with transversal T and T^{†} rotations on its physical qubits.